United States : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
This Selected Issues paper on the United States explains the behavior of inflation and unemployment during 1997-98. The paper highlights that a simple Philips curve equation relating inflation to the unemployment gap has overpredicted inflation since 1993. The mean forecast error for 1994-97 is greater than zero by an amount equivalent to two-thirds of the standard deviation of the forecast error. The paper also examines the developments in the U.S. stock prices. Alternative approaches to social security reform are also discussed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet